LaTeX tutorial for the standardization and automation of population analysis reports - Thomas Frank (Wiley, 2021)
Abstract Writing population analysis reports that fulfilling the specifications of submission readiness is a time‐consuming process and prone to human error. Thus, there is a need to streamline the creation of these reports through elements of standardization and automation. LaTeX is considered a suitable program package capable of creating long, modular, structured documents, and, because of its typographic quality, includes formula typesetting. The presented automation scripts together with easily adjustable LaTeX templates are designed to enable the reader to understand and reproduce a typical workflow from analysis to reporting. The focus of this tutorial is to use an example of a population pharmacokinetic analysis to show how to work with the proposed automated structures allowing even a reader new to the concept of LaTeX to automatize the reporting workflow and customize the templates for their specific needs.